Studi Komparasi Fase Vegetatif Tanaman Utama Varietas Padi Berpotensi Ratun Tinggi di Lahan Pasang Surut - Novisrayani Kesmayanti; Evriani Mareza (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2015)
Rice ratoon system is one solution constraints of tidal rice fields, particularly the season and limitations of agricultural inputs. The ratoon’s quality highly dependent on the quality of main crop’s vegetative phase. The main crop with maximum vegetative phase, is predicted to produce high growth of ratoon. This study is the second phase of the three experimental stages of multi-year research of hibah bersaing. The first phase of the experiment (September 2013-May 2014) aims to give the height of singgang’s cutting to increase vigor vegetative and reproductive phase of ratoon in tidal land. This experiment is to obtain adaptive rice varieties with high potentially of ratoon in tidal rice fields. This experiment used a randomized block design factors, namely rice varieties (Sintanur, Margasari, Mekongga and Batanghari), with three replications, ongoing since March 2014-September 2014, located in experimental farm of Faculty of Agriculture, IBA University, in Palembang. Each treatment consists of 18 units of plant, so totaly contained 216 experimental units. Rice plants grown in soil media of tidal rice fields that brought from Telang Sari village, Tanjung Lago district, Banyu Asin regency, South Sumatera. The vegetative parameters consist plant height, panicle height, number of tillers, number of productive tillers, chlorophyl, flag leaf area and leaf area. The results indicate that the vegetative phase of Sintanur is the best, measured by plant height and panicle being, number of tillers and productive tillers highest, and flag leaf area and the largest leaf area. This experimental results imply that the quality of growth and vigor of Sintanur’s ratoon would be better than Margasari, Mekongga and Batanghari.